2013
DOI: 10.1038/nature11925
|View full text |Cite
|
Sign up to set email alerts
|

NANOG-dependent function of TET1 and TET2 in establishment of pluripotency

Abstract: Molecular control of the pluripotent state is thought to reside in a core circuitry of master transcription factors including the homeodomain-containing protein Nanog1–2, which plays an essential role in establishing ground state pluripotency during somatic cell reprogramming3–4. While the genomic occupancy of Nanog has been extensively investigated, comparatively little is known about Nanog-associated proteins5 and their contribution to the Nanog-mediated reprogramming process. Using enhanced purification tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
396
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 397 publications
(415 citation statements)
references
References 27 publications
17
396
0
2
Order By: Relevance
“…That study further showed that smallmolecule antagonists of RA signaling attenuate β-catenin and activate Wnt signaling in EpiSCs, thus providing a likely mechanism for how RA enhances reprogramming. We suggest that in addition to this effect, RA signaling enhances reprogramming by directly activating TET2 expression, a known reprogramming factor (16,18).…”
Section: Retinol and Ascorbate Enhance Reprogramming Of Epiblast Stemmentioning
confidence: 99%
See 1 more Smart Citation
“…That study further showed that smallmolecule antagonists of RA signaling attenuate β-catenin and activate Wnt signaling in EpiSCs, thus providing a likely mechanism for how RA enhances reprogramming. We suggest that in addition to this effect, RA signaling enhances reprogramming by directly activating TET2 expression, a known reprogramming factor (16,18).…”
Section: Retinol and Ascorbate Enhance Reprogramming Of Epiblast Stemmentioning
confidence: 99%
“…TET proteins can contribute to locus-specific demethylation in nESCs (1,14), and their depletion reduces the expression of pluripotency genes and increases methylation at their promoters (12,15). Furthermore, forced expression of TET1 and TET2 dramatically enhances iPSC reprogramming in a catalytically dependent manner (16)(17)(18). Nevertheless, the molecular signals that control TET activity in nESCs, and how they can be manipulated during reprogramming, are poorly characterized.…”
mentioning
confidence: 99%
“…Co-expression of NANOG and TET1 increased the genome-wide levels of 5hmC. This process is dependent on NANOG-mediated recruitment of TET1 to NANOG-binding sites, suggesting that NANOG cooperates with TET1 in DNA demethylation at specific genomic loci during reprogramming [7]. Interestingly, another study discovered that TET2 and poly (ADP-ribose) polymerase-1 (PARP-1) cooperatively fine-tune epigenetic modifications and upregulate expression of the pluripotency genes Nanog and Esrrb in the early stage of somatic cell reprogramming [8], indicating a role of TET proteins in the regulation of pluripotency genes' expression as well as their activity.…”
mentioning
confidence: 97%
“…However, little is known about its interacting partners that may contribute to the induction of pluripotency in pre-iPSCs. To identify the interacting partners of NANOG, Costa et al [7] utilized NANOG as bait to identify its physically associated partners via enhanced affinity purification followed by mass spectrometry. TET1 was identified as one of 27 high-confident partners in mESCs.…”
mentioning
confidence: 99%
“…For a long time the active process was unknown, however in 2011 studies showed that the responsibility for such process is the formation of 5-hydroxymethylcytosine (5-hmc), a cytosine variation, in which a -OH is added to the methylated cytosine by a protein from the Tet family; Tet 1, 2 or 3 (IQBAL et al, 2011;WOSSIDLO et al, 2011). Tet 1 and 2 have been related to embryonic stem cells pluripotency and depletion of Tet1 implicates in lineage differentiation difficulties (COSTA et al, 2013). Additionally, Tet 1 was detected in primordial germ cells highlighting its role in an undifferentiated profile (HAJKOVA et al, 2010), and Tet 3 is highly expressed in both oocyte and zygote, being responsible for 5-hmc increase on paternal pronucleus, while the maternal genome is protected by binding to PGC7 protein (also known as Dppa3 or Stella) (IQBAL et al, 2011;WOSSIDLO et al, 2011).…”
Section: Epigenetic Mechanisms Of Natural Reprogramming Versus Cloningmentioning
confidence: 99%